ASR: Archival Solar Flares Catalog - M. Berretti; S. Mestici; L. Giovannelli; D. Del Moro; M. Stangalini; F. Giannattasio; F. Berrilli (The Astrophysical Journal Supplement Series)
Solar flares result from the rapid conversion of stored magnetic energy within the Sun’s corona. These energy releases are associated with coronal magnetic loops, which are rooted in dense photospheric plasma and are passively transported by surface advection. Their emissions cover a wide range of wavelengths, with soft X-rays being the primary diagnostic for the past 50 years. Despite the efforts of multiple authors, we are still far from a complete theory capable of explaining the observed statistical and individual properties of flares. Here, we exploit the availability of stable and long-term soft X-ray measurements from NASA’s Geostationary Operational Environmental Satellites mission to build a new solar flare catalog, with a novel approach to linking sympathetic events. Furthermore, for the most energetic events since 2010, we have also provided a method to identify the origin of the observed flare and eventual link to the photospheric active region by exploiting the array of instruments on board NASA’s Solar Dynamic Observatory. Our catalog provides a robust resource for studying space weather events and training machine learning models to develop a reliable early warning system for the onset of eruptive events in the solar atmosphere.